The element of market orientation is the organization – internal marketing - Akimbaeva K.T., Karimova M.D. Alshynbay A.M. (Journal of Economic Research & Business Administration, 2016)
The marketing function is one of the management functions of the organization, which has as its ultimate goal the increase in sales and therefore profits. To better achieve market objectives, the organization needs to be simultaneously focused on internal and external market. External customers are the focus of external marketing and employees of the organization are called internal customers, internal marketing. The main task of leadership is to pursue a balanced external and internal marketing policies. For the effective functioning of the organization requires a balanced internal and external marketing policies. The process of creating a services organization is equivalent to a into account the interests and needs of external and internal customers. Object orientation on internal customer relationships are between individual employees, departments and management in the process of value chain services.